Price, Brand Image, and Halal Certification as Determinants of Muslim Consumers’ Purchase Decisions for Sate Ayam H. Tukri Sobikun Ponorogo - Rizqullah, Maula Falih; Imari, Iqbal (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2025)
The Indonesian people widely consume satay as one of their culinary delights. Ponorogo is one of the cities in Indonesia where there are satay restaurants. One of the most dominated places by visitors is Sate Ayam H. Tukri Sobikun Ponorogo. This study aims to measure the effect of price, brand image, and halal certification on Muslim purchasing decisions for Sate Ayam H. Tukri Sobikun Ponorogo and how significant the effect is. This research was conducted by distributing questionnaires to 155 respondents of Sate Ayam H. Tukri Sobikun Ponorogo consumers in Ponorogo with the sample selection method being non-probability sampling of the Purposive Sampling type, where the sample was selected based on people who were easy to meet and willing to cooperate. The analysis tool was used to measure the effect of price, brand image, and halal certification on Muslim Purchasing Decisions is multiple linear regression analysis and the data is processed using the SPSS program. The results showed that Price has a significant effect on Muslim purchasing decisions at sate ayam H. Tukri Sobikun Ponorogo, brand Image has a significant effect on Muslim purchasing decisions at sate ayam H. Tukri Sobikun Ponorogo, halal certification has no significant effect on Muslim purchasing decisions sate ayam H. Tukri Sobikun Ponorogo.